2016
DOI: 10.18267/j.polek.1118
|View full text |Cite
|
Sign up to set email alerts
|

Wages Development and its Non-Equality by ICT Professionals in the Czech Republic

Abstract: Wages Development and its Non-Equality by ICT Professionals in the Czech RepublicThis article analyses wages development in the Czech Republic since 2000 to 2014. Analysis is principal focused on ICT Professional's (this group of employees in the economy is split into two sub groups ICT Specialists and ICT technicians) wages and its comparison to the wages in the whole Czech economy. Used data sources were collected by Ministry of Labour and Social Aff airs of the Czech Republic, in the "Information System of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Our data include outliers, especially wages above EUR 4,000. However, these wages, which are relatively rare, significantly influence the total volume of wages (Marek and Doucek, 2016). In our case, they significantly increase the average wage.…”
Section: Processing Methodsmentioning
confidence: 48%
See 1 more Smart Citation
“…Our data include outliers, especially wages above EUR 4,000. However, these wages, which are relatively rare, significantly influence the total volume of wages (Marek and Doucek, 2016). In our case, they significantly increase the average wage.…”
Section: Processing Methodsmentioning
confidence: 48%
“…Torrent-Sellens (2008) and the conclusions of his study confirm this fact especially in terms of an increase in job opportunities and wages in various ICT professions. The wages of ICT Professionals tend to be higher than average wages in economies (Torrent-Sellens, 2008;Marek and Doucek, 2016); this fact also opens up the issue of equal pay for equal work -that is, the issue of equality in remuneration for ICT Professionals' work not only in the economy but also in heterogeneous work teams comprising of men and women (Simard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The second part of our article discusses the issue of ICT Professionals and the trend of the gender pay gap among them. The current studies concerning the gender pay gap in the Czech Republic include in particular (Marek, Doucek, 2016). As our research has shown, it depends on whether ICT Professionals work in the private sector or in the public sector.…”
Section: Gender Pay Gap In the Czech Economymentioning
confidence: 92%
“…The second group of studies focuses on the trend of certain segments in the economy. For conditions of the Czech Republic for example (Nedomova at al., 2017, Marek at al., 2018. The study Bergmann at al.…”
Section: Introductionmentioning
confidence: 99%